Упростить выражение. 1) 2a (3a-5) - (a-3) (a-7) 2) (x-3) (4x^2-6x) - 2x (2x-5) (x-2)

0 голосов
23 просмотров

Упростить выражение. 1) 2a (3a-5) - (a-3) (a-7) 2) (x-3) (4x^2-6x) - 2x (2x-5) (x-2)


Алгебра (66 баллов) | 23 просмотров
Дан 1 ответ
0 голосов

1)
2a(3a - 5) - (a - 3)(a - 7) = 2a \times 3a - 2a \times ( - 5) - ( {a}^{2} - 3a - 7a + 21) = 6 {a}^{2} + 10a - {a}^{2} + 10a - 21 = 5 {a}^{2} + 20a - 21
2)
(x - 3)(4 {x}^{2} - x) - 2x(2x - 5)(x - 2) = 4 {x}^{3} - 12 {x}^{2} - {x}^{2} + 3x - 2x(2 {x}^{2} - 5x - 4x + 10) = 4 {x}^{3} - 13 {x}^{2} + 3x - 4 {x}^{3} + 18 {x}^{2} - 20x = 5 {x}^{2} - 17x

(41.5k баллов)